PEMBAHARUAN PENDIDIKAN MENURUT PEMIKIRAN HARUN NASUTION - Moh Afifur Rahman (AHSANA MEDIA: Jurnal Pemikiran, Pendidikan dan Penelitian Ke-Islaman, 2020)
The big problem faced by Muslims is when it has to be faced with Western cultures. And the value of Islamic culture is shifted because of the lack of power owned by Muslims. Renewal of Islamic education can be said as an attempt to make improvements to the better order of Islamic education system. By connecting the reality of the developing times with existing systems, so it can be expected to facilitate and precisely on the target of Islamic education that relevance. Aaron Nasution's strategy in renewal of Islamic education came into the order of Islamic education curriculum, he wanted to change the pattern of classical Islamic education approach to modern Islamic education pattern. Harun Nasution in the construction of Islamic education in Indonesia, namely the birth of the "Aaronic movement". In which it contains three different opinions: first, put a fundamental and universal understanding of Islam. Second, revise the entire curriculum of higher education units throughout Indonesia. Third, strive for development in the institutional sphere.